The Influence of School Factors on Students' Mathematics Achievements in Trends in International Mathematics and Science Study (TIMSS) in Abu Dhabi Emirate Schools - Yousef Wardat; Shashidhar Belbase; Hassan Tairab; Rachel Alison Takriti; Maria Efstratopoulou; Hamza Dodeen (MDPI AG, 2022)
This study aimed to explore school factors that influence students' achievements in Trends in International Mathematics and Science Study (TIMSS) in schools in the Emirate of Abu Dhabi, in the United Arab Emirates. The study sample for TIMSS 2015 consisted of 4838 students in eighth grade; 2172 girls, 2666 boys, and 156 schools from Abu Dhabi attended and participated in TIMSS 2015. Principal component analysis (PCA) was run on 77 items of school questionnaires administered to school principals to provide information about the school contexts for teaching and learning. The five factors from the school questionnaire were general school resources, school discipline and safety, parental support, principal experience and education, and library and instruction resources. Multiple regression models were implemented to examine the impact of school factors on student achievement in TIMSS 2015. The models are statistically significant, indicating that they fit the data well. This also demonstrates a significant linear relationship between students' achievement in TIMSS 2015 and the variables related to school factors.